Dehiscence rate in wound closed with cyanoacrylate and black braided silk after surgical removal of impacted third molar: A systematic review and meta‐analysis. (29th March 2021) - Raut, Vaibhav D.; Kumar, Santhosh; Raut, Sanyukta; Bhate, Kalyani; Singh, Manju; Kakodkar, Pradnya; Waknis, Pushkar
Abstract: Aim: To perform a systematic review and meta‐analysis of dehiscence rate in wound closed with cyanoacrylate and black braided silk after surgical removal of impacted third molar. Materials and Methods: This review is based on PRISMA guidelines and the review protocol was registered in PROSPERO (CRD42019097294). An electronic search of PubMed (Medline), Google Scholar, Cochrane database, EbSCOhost, cross referencing and hand search of journals was carried out. The studies published in English literature from 1 January 2008 to 31 March 2019, where wound closure was done using black braided silk suture and cyanoacrylate following third molar surgery, and those reporting dehiscence rate after a minimum follow‐up of 7 days, were included. The event of occurrence of dehiscence in the two groups was used to calculate the risk ratio using the random effects model (Mantel–Haenszel model) at 95% CI. Results: Of the 309 articles, three unique studies were identified for the review. Of these, two were randomized controlled trials. A total of 190 patients were included in these three trials. Total of seven events of dehiscence were observed in the cyanoacrylate group as compared to eight in the suture group. The meta‐analysis results indicate that there was no statistically significant difference in the dehiscence rate, RR 0.74, 95% CI (0.13–4.13), with a heterogeneity of I 2 = 56%. Conclusion: There is no difference in the dehiscence rate of wound closed with cyanoacrylate and black braided silk suture.